Circadian Phase-Shifting Effects of Bright Light, Exercise, and Bright Light + Exercise - Youngstedt, Shawn D. (J Circadian Rhythms, 2016)
Limited research has compared the circadian phase-shifting effects of bright light and exercise and additive effects of these stimuli. The aim of this study was to compare the phase-delaying effects of late night bright light, late night exercise, and late evening bright light followed by early morning exercise. In a within-subjects, counterbalanced design, 6 young adults completed each of three 2.5-day protocols. Participants followed a 3-h ultra-short sleep-wake cycle, involving wakefulness in dim light for 2h, followed by attempted sleep in darkness for 1 h, repeated throughout each protocol. On night 2 of each protocol, participants received either (1) bright light alone (5,000 lux) from 2210–2340 h, (2) treadmill exercise alone from 2210–2340 h, or (3) bright light (2210–2340 h) followed by exercise from 0410–0540 h. Urine was collected every 90 min. Shifts in the 6-sulphatoxymelatonin (aMT6s) cosine acrophase from baseline to post-treatment were compared between treatments. Analyses revealed a significant additive phase-delaying effect of bright light + exercise (80.8 ± 11.6 [SD] min) compared with exercise alone (47.3 ± 21.6 min), and a similar phase delay following bright light alone (56.6 ± 15.2 min) and exercise alone administered for the same duration and at the same time of night. Thus, the data suggest that late night bright light followed by early morning exercise can have an additive circadian phase-shifting effect.